2018
DOI: 10.1111/cid.12604
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled clinical trial to assess crestal bone remodeling of four different implant designs

Abstract: From this RCT, it is concluded that the implant-abutment connection and a microthreaded external thread configuration have limited influence on crestal bone remodeling. The latter can be considered a multifactorial process and is more dependent on other factors such as biologic considerations than on implant design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 36 publications
0
39
0
Order By: Relevance
“…in vitro studies applying static and dynamic loading to implants with different connections have, however, shown leakage also from the conical connection . Furthermore, a controlled clinical study showed no differences when comparing the same implant design with or without a conical connection after a follow‐up of 19 months . In the present study, minimal bone loss was observed in spite of the fact that the implant‐prosthesis junction was placed close to the bone level, which theoretically would have challenged the biologic width and resulted in more bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…in vitro studies applying static and dynamic loading to implants with different connections have, however, shown leakage also from the conical connection . Furthermore, a controlled clinical study showed no differences when comparing the same implant design with or without a conical connection after a follow‐up of 19 months . In the present study, minimal bone loss was observed in spite of the fact that the implant‐prosthesis junction was placed close to the bone level, which theoretically would have challenged the biologic width and resulted in more bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies, at high and unclear risk of bias established, a comparative analysis between rough collar implants with and without microthreads (Glibert et al, ; Kang et al, ; Lee et al, ; Ryu et al, ). One study evaluated the position of microthreads within the collar on marginal bone levels (Song et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In seven studies, it was unclear whether random sequence gen- In 18 cases, it was unclear from the trial report whether concealment of the randomization was performed (Akoglu et al, 2011;Astrand, Engquist, Anzen, et al, 2004;Glibert et al, 2018;Guarnieri et al, 2015;Gultekin, Gultekin, Leblebicioglu, Basegmez, & Yalcin, 2013;Hegazy, Elmekawy, & Emera, 2016;Hof et al, 2014;Hsu et al, 2016;Jacobs et al, 2010;Kang et al, 2012;Kim et al, 2010;Lee, Choi, Park, Kim, & Moon, 2007;Penarrocha-Diago et al, 2013;Ravald, Dahlgren, Teiwik, & Grondahl, 2013;Ryu, Namgung, Heo, Lee, & Lim, 2016;Shin, Han, Heo, Kim, & Chun, 2006;Song et al, 2009;Tymstra et al, 2011) and were therefore classified as unclear risk for it the possibility to foresee the allocation. One study reported alternate enrolment of patients and was classified as high risk of bias (Nickenig et al, 2013).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations